Newsday (1979)
[00:00:05] National News; gasoline rationing protocols from the Energy Department [00:01:30] State News [00:02:10] Crime News [00:02:39] An Hour With spot [00:03:11] Mike Lurry with a story about FBI domestic espionage [00:04:58] State News [00:06:09] United Farm Workers strike [00:06:58] National News [00:07:17] Bob Hahn with a story about a medical computer [00:08:06] Weather [00:08:21] Pam Mark Hall at the First Baptist Church spot [00:08:52] Roger Heath interviewed about upcoming symphonic band concert [00:09:59] Cal Poly News; Iranian students' financial troubles caused by revolution [00:10:50] Cal Poly recreation Skate-A-Thon [00:11:20] Upcoming performances in the University Union [00:11:45] Central Coast News [00:12:06] Wilbur Shigahara on untimely rains [00:12:54] Allan Bond, city council candidate [00:13:24] Leslie Bensacca interviews city council candidate Liz Fisher [00:13:59] 91 News from A to Z - To Acquit or Not to Acquit [00:15:08] Sequoia Hall Dance spot [00:15:39] Sports news with Jay Birks [00:19:34] Bernie Harr interviewed by Steve Stratt [00:19:53] Sports news ends [00:20:02] Leslie on state news; farm workers strike [00:21:16] Paula Chambers on Kennedy Library construction [00:23:37] FDA Microwave spot [00:24:10] 91 News from A to Z - Simulation and a Real Crash [00:26:07] Tim Tomastik, Chuck Swino, Frank Thomas with an overview of news [00:26:50] Magic Mountain spot [00:27:48] Liz Nevins on Ambrosia concert [00:28:20] Chinese-American exhibit "Journeys Came, Journeys Went"; Dr. Kreager interviewed [00:29:26] Upcoming Buffo the Mime act [00:29:46] Local news; Glover Avery death [00:30:20] Grover City welfare fraud [00:31:40] Nancy Bauer with Clell Welchell interview for City Council part 4 of 7 [00:32:08] Weather [00:32:38] Tri-Counties Blood Bank PSA [00:33:08] National News; Carter on rationing authority; Mideast peace talks [00:34:04] Paula Chambers on the Cal Poly Travel Center [00:36:40] World News with Frank Thomas; St. Chris oil fire; Longwood Elementary carbon monoxide; Israeli Prime Minister arriving [00:38:10] World News; China in Vietnam [00:39:18] Bruce Tochars on dental fees in California [00:40:20] Anti-smoking PSA [00:40:46] EOC Energy Program PSA [00:41:24] California News [00:42:08] Paula Chambers with report on Bobby Jimenez [00:43:42] Cataract PSA [00:44:42] 91 News from A to Z - Nixon Navicare Nixed? [00:45:54] Sports news with Jay Birks [00:50:06] Kelly Pierce with Steve Miller, track coach [00:52:13] State News with Frank Thomas [00:53:29] Paula Chambers on vegetarianism [00:57:16] American Optometry Association PSA [00:57:48] 91 News from A to Z - For the Love of Music and Giant Sundae [00:59:30] Tim Tomastik, Chuck Swino, Missy Arnold [00:59:40] Missy Arnold on proposed energy cuts [01:00:56] KCPR Statewide Concert Scene PSA [01:01:00] Missy Arnold continues discussing energy cuts [01:03:42] World News; Swiss Alpine Rescue; [01:04:00] Election Discussion [01:05:47] California News; Newton trial; Spencer arraignment [01:06:20] Workers Rights PSA; Father Ed Stanton [01:07:01] Paula Chambers on Geothermal Energy [01:09:34] Lee Martin Trial; Huey Newton Trial; [01:12:06] Walter Fogel on illegal aliens from USC news service) [01:13:18] Weather [01:13:56] Veterans Affairs PSA [01:14:20] Laser show coming to Cal Poly [01:15:00] City Council Interviews continue with Leslie Bensacca [01:15:44] Nuclear Fusion talk upcoming [01:16:25] Kevin Riggs on Point Conception land dispute [01:16:55] 91 News from A to Z - Dog Tags for All [01:18:31] Sports news with Jay Birks [01:20:13] Steve Miller interviewed about his public speaking career [01:23:11] Sports news ends [01:23:15] State News; education department legislation; [01:24:13] Paula Chambers on Solar Energy [01:26:53] 91 News from A to Z - Whenever You Want To [01:28:27] Paula Chambers, Donna Penbrook, Jay Birks [01:28:44] Campus News with Jay Birks [01:29:22] Magic Mountain spot [01:30:18] Brad Fultermeyer on Human Understanding and Growth Committee Retreat [01:31:25] Campus film about Gertrude Stein [01:33:41] Local News [01:34:43] Gus Thomason interviewed by Nancy Bauer [01:35:03] Weather [01:35:33] Water Conservation PSA [01:36:01] National and World News [01:37:08] Racquetball story by Wayne Jackson with interviews [01:39:41] Crime PSA [01:40:42] National News [01:43:10] Greg Santos from American Medical Association on alcohol abuse [01:44:25] Wadell trial and crime news [01:45:49] Crime news continues [01:46:16] Workplace safety PSA [01:47:21] 91 News from A to Z - Schooling [01:48:34] Sports news